2013
DOI: 10.1039/c3nr03319h
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanorods as multifunctional probes in a liquid crystalline DNA matrix

Abstract: We show how a single gold nanorod can serve as a multifunctional probe in an organized DNA matrix. Polarization analysis of two-photon luminescence excited with a femtosecond laser enables imaging of the orientation of a single nanorod, which reports the orientation of DNA strands. Carefully controlled photoinduced heating by the same laser is able to degrade the DNA matrix in a highly localized volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Optical measurements of gold nanoparticles, such as characterization of nonlinear optical properties (e.g. with Z-scan technique 18 ) or imaging by two-photon microscopy, 19 require information concerning the stability of nanorods illuminated with pulsed laser beams. Moreover, the long-term stability of NRs is needed for various nanorod applications, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Optical measurements of gold nanoparticles, such as characterization of nonlinear optical properties (e.g. with Z-scan technique 18 ) or imaging by two-photon microscopy, 19 require information concerning the stability of nanorods illuminated with pulsed laser beams. Moreover, the long-term stability of NRs is needed for various nanorod applications, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The same conclusions concerning the formation and appearance of a columnar hexagonal phase with a periodic zigzag pattern in dried droplets of DNA solution doped with gold NRs were previously drawn by our research group. 11 Thermal stability of DNA LCs Polarized light microscopy (PLM) is one of the most common tools used for the investigation of liquid crystalline phases, which allows differentiation between various LC textures and also the study and observation of phase transitions as a function of temperature. Transformation between different mesophases is the result of the order parameter change.…”
Section: Columnar Hexagonal Phasesmentioning
confidence: 99%
“…[10][11][12][13][14] It is still quite an unexplored area of research, where so far De Sio et al proved that DNA LCs were able to organize gold NRs within DNA LCs deposited on a glass substrate by drop casting and allowed to dry, 10 and Yevdokimov et al showed the formation of linear clusters of small gold nanopartciles (with diameter around 2 nm) in a cholesteric liquid crystalline dispersion of DNA. 14 However, the properties of a composite material consisting of gold NRs with strong plasmon resonances dispersed in DNA lyotropic LCs prepared in closed glass cells, where the type of observed phases and molecular organization are different compared to previously mentioned DNA LCs, [10][11][12][13][14] have not been studied in detail yet. Lacaze et al showed that it is possible to order small nanoparticles using smectic LCs 15 and our intent was to check this ability for DNA LCs, but it is necessary to evaluate the basic properties of DNA LC-nanoparticle hybrid systems first.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic gold nanoparticles (AuNPs), gold nanoclusters, and Au(I) complexes have distinct optical features as a result of their differences in size, structure, and bonding. Therefore, understanding Nanomaterials 2019, 9, 933 2 of 13 the photodynamics will help to deepen the understanding of their electronic structures and optical properties [2,7,9,12,[16][17][18]. The electron dynamics of plasmonic gold nanoparticles has been intensively investigated [19,20].…”
Section: Introductionmentioning
confidence: 99%